Case report: Strategies for improving outcomes in patients with primary ovarian small-cell neuroendocrine carcinoma - Li, YingYing; Wu, Yueling; Zhang, Ying; Li, Xiaofang (Frontiers in Oncology, 2022)
Small-cell neuroendocrine carcinoma (SCNEC) of the ovary is a gynecological malignancy characterized by rapid progression and poor prognosis. SCNEC is divided into primary and metastatic tumor. Primary ovarian neuroendocrine cancer is extremely rare and has a low 5-year survival rate. This paper reports the clinical manifestations of a 58-year-old patient with primary ovarian Small-cell neuroendocrine carcinoma and the prognosis after surgical adjuvant chemotherapy. The prevailing literature on this carcinoma is also reviewed and summarized. Our analysis reveals that histopathological examination is the standard diagnostic tool for ovarian SCNEC. We also highlight the importance of comprehensive imaging evaluation, early pathological diagnosis and comprehensive aggressive treatment to the prognosis of patients.